MicroRNA-181b-5p/HEY2 axis is involved in the progress of deep venous thrombosis via mediating vascular endothelial injury - Dawei Zhang; Cheng Cheng; Meiying Yang; Xiuyin Zhang; Xinming Yu; Min Wang (Hematology)
Objectives: Deep-venous thrombosis (DVT) refers to abnormal blood clotting in the deep vein cavity, and post-thrombotic syndrome (PTS) is the most frequent complication. The study explored the impact of microRNA 181b-5p on DVT progression based on human umbilical vein endothelial cells (HUVECs).Methods: Levels of miR-181b-5p were examined in 150 cases with acute lower extremity DVT. ROC curve and K-M plot were drawn for clinical value assessment. The role of miR-181b-5p in HUVECs viability, migration, apoptosis, inflammatory response and adhesion factors’ release was investigated. Target gene of miR-181b-5p was predicted, and its role in cell function was explored.Results: Low-expressed miR-181b-5p showed favorable diagnostic performance in differentiating DVT with the AUC of 0.948. Patients with low miR-181b-5p had a high incidence of PTS. miR-181b-5p overexpression promoted HUVECs’ viability and migration, while inhibiting cell apoptosis and release of inflammatory and adhesion cytokines. As the target gene of miR-181b-5p, HEY2 overexpression reversed the role of miR-181b-5p in HUVECs.Conclusion: MiR-181b-5p serves as a potential biomarker for DVT diagnosis and PTS development. Overexpression of this miRNA targeted HEY2 to alleviate endothelial cell damage.